Quality of Life and Factors Affecting It: A Study Among People Living Near a Solid Waste Management Facility - Phan, Long Thanh; Nguyen, Gia Thanh; Nguyen, Quynh Anh Dac; Nguyen, Hieu Song; Nguyen, Tin Trung; Watanabe, Toru (Frontiers in Public Health, 2021)
Background: The amount of waste generated has been increasing over the years. Meanwhile, the capacity of solid waste management facilities (SWMFs) for waste disposal does not meet the needs, resulting in adverse consequences on the natural environment and health of residents living near these plants, which can significantly degrade their quality of life (QoL). This study aims to evaluate the QoL of residents living near an SWMF and the potential impacts it has on the residents. Methods: A cross-sectional descriptive study was conducted involving 801 subjects, aged 18 and above, who live near the SWMF of Hue City, Vietnam. The QoL of the subjects was quantitatively assessed using the WHO QoL assessment scale (WHOQOL-BREF). The general, health, and environmental factors influencing QoL were identified using bivariate and multivariate logistic regression analyses. Results: About 22.6% of the subjects had a good QoL. In particular, the proportions for good psychological health (6.9%) and environment (13.6%) were low, indicating an influence of the SWMF. Significant factors that degraded the QoL of residents were less education defined by not graduating from high school (odds ratio, OR = 2.78; 95% CI = 1.09–7.06), poor health status (OR = 2.50; 95% CI: 1.56–4.01), dissatisfaction with water quality (OR = 2.41; 95% CI: 1.10–5.25), and unacceptance of the SWMF presence (OR = 1.70; 95% CI: 1.11–2.60). Moreover, subjects living within 2 km of the plant had dermatological diseases and digestive disorders more frequently than those who lived away from the plant. They also reported more complaints regarding water, air, and soil quality, which were likely due to the operation of the SWMF. Conclusions: Burying and disposing of solid waste at the SWMF might lead to the degradation of the surrounding water and soil environments, and its collection and transportation are considered to cause odor and dust. The efforts of responsible authorities to strictly supervise and inspect these activities at the SWMF are essential, not only to protect the surrounding environment but also to improve the QoL of those who live nearby these plants.